2021
DOI: 10.1007/s10549-021-06314-4
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life of early-stage breast cancer patients after different radiotherapy regimens

Abstract: Purpose To evaluate and compare health-related quality of life (HRQL) of women with early-stage breast cancer (BC) treated with different radiotherapy (RT) regimens. Methods Data were collected from five prospective cohorts of BC patients treated with breast-conserving surgery and different RT regimens: intraoperative RT (IORT, 1 × 23.3 Gy; n = 267), external beam accelerated partial breast irradiation (EB-APBI, 10 × 3.85 Gy; n = 206), hypofractionated who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
(46 reference statements)
0
5
0
1
Order By: Relevance
“…45 Contrastingly, radiotherapy treatment did not substantially improve the health-related quality of life in early-stage breast cancer patients. 46 However, endocrine therapy with aromatase enzyme inhibitors had a significant positive association with most health-related quality of life domains. 47 Previous systematic reviews reported that breast cancer patients with metastatic disease had a worse health-related quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…45 Contrastingly, radiotherapy treatment did not substantially improve the health-related quality of life in early-stage breast cancer patients. 46 However, endocrine therapy with aromatase enzyme inhibitors had a significant positive association with most health-related quality of life domains. 47 Previous systematic reviews reported that breast cancer patients with metastatic disease had a worse health-related quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Работа проведена для того, чтобы выявить преимущества протокола TARGIT, по сравнению с ДЛТ у больных РМЖ на ранних стадиях. Общее количество пациентов составило 2298, в группе ИОЛТ пятилетний риск локального рецидивирования составлял 2,1%, а в группе ДЛТ -1,1%, что не имеет статистически значимых различий [32].…”
Section: сегодняunclassified
“…Most observational studies evaluating fatigue in breast cancer patients have been cross‐sectional studies that focused on acute fatigue, with assessments up to 6 months after treatment completion. Only a small proportion evaluated CRF beyond 6 months and, from those, even fewer focused on RT‐treated patients 8‐11 . More than 20 different instruments have been employed to evaluate CRF, contributing to a large heterogeneity in its measurement 12 .…”
Section: Introductionmentioning
confidence: 99%